How Does Exposure to Mass Media affect HIV Testing and HIV-Related Knowledge Among Adolescents? Evidence From Uganda - Bago, Jean-Louis; Lompo, Miaba, Louise (My University, 2018)
Sexual and reproductive health remains one of the greatest challenges in developing countries. In Uganda, adolescents are the most vulnerable group as far as HIV epidemic is concerned. Mass media awareness campaigns play a key role in promoting sexual and reproductive health among adolescents. Using Uganda’s 2016 Demographic Health Survey, we examine the causal effect of mass media exposure on the probability of adolescents getting an HIV test and their HIV-related knowledge. Our results suggest that the exposure to mass media increases both adolescents’ likelihood to get tested for HIV and their HIV-related knowledge score. In fact, we find that reading newspapers once a week increases the likelihood of an adolescent to test for HIV by 6.29 percentage points. Listening to radio once a week increases the probability to test for HIV by 4.57 percentage points. This effect increases to 6.56 percentage points when the adolescent listens to the radio more than once a week. Watching TV more than once a week increases adolescents’ probability to get tested for HIV by 8.57 percentage points. For HIV-related knowledge, we find that compared to adolescents who do not read newspapers at all, adolescents who read newspapers less than once a week and those who read newspapers at least once a week have a higher score of HIV-related knowledge of 9.12% and 9.64% respectively. Compared to adolescents who do not listen to radio at all, adolescents who listen to radio less than once a week have a higher (5.88%) score of HIV related knowledge. Moreover, listening to radio at least once a week increases the score of HIV-related knowledge by 5.52%. Hence, mass media awareness campaigns are important policies to promote HIV testing and HIV-related knowledge among adolescents in Uganda.
Keywords: mass media; HIV testing; HIV-related knowledge; adolescents; Uganda